The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5535/arm.2018.42.3.441
|View full text |Cite
|
Sign up to set email alerts
|

The Changes of CTX, DPD, Osteocalcin, and Bone Mineral Density During the Postmenopausal Period

Abstract: ObjectiveTo investigate appropriate treatment time and useful bone turnover markers (BTMs) for monitoring bone turnover during the postmenopausal period, we analyzed changes of two bone resorption markers; serum carboxyterminal telopeptide of collagen I (s-CTX), urine deoxypyridinoline (u-DPD), one bone formation marker; serum osteocalcin (s-OC), and bone mineral density (BMD) in Korean postmenopausal women.MethodsSeventy-eight menopausal women were divided into three groups according to postmenopausal period:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 21 publications
2
26
0
2
Order By: Relevance
“…In concert with decreases in estrogen, both bone formation and bone resorption are greatest at 7-8 years after menopause [30], correlating well with the acceleration of bone turnover observed in the osteopenia and osteoporosis groups in the present study. Moreover, osteoporosis group individuals had lower BMD than both control and osteopenia group individuals, and the cumulative loss was greater at the lumbar spine than at the hip.…”
Section: Agingsupporting
confidence: 87%
“…In concert with decreases in estrogen, both bone formation and bone resorption are greatest at 7-8 years after menopause [30], correlating well with the acceleration of bone turnover observed in the osteopenia and osteoporosis groups in the present study. Moreover, osteoporosis group individuals had lower BMD than both control and osteopenia group individuals, and the cumulative loss was greater at the lumbar spine than at the hip.…”
Section: Agingsupporting
confidence: 87%
“…They are ideal tools to evaluate the actual metabolic status of the bone, as well as a well-established result of abnormal metabolism (5). Table 1 shows the most reviewed bone biomarkers to assess the different phases of bone metabolism process (4,(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that bone resorption reaches its peak in 5 to 10 years after the onset of postmenopause compared with the years before and after that timeframe. (43) In the aforementioned study, (39) the women were postmenopausal for at least a year, whereas in our study, for at least 5 years. Thus, we could argue that the observed relationship between folate and CTx-1 in these two studies was affected by the years since the onset of postmenopause, as well as possible differences in diet, considering that the two cohorts resided in different geographic locations.…”
Section: Discussionmentioning
confidence: 57%